Rancang Bangun Sistem Mekanik 3D Printer Mortar 1x1x1 m - Muhammad Tomy Adam; Sonki Prasetya; Djoko Nursanto; Ahmad Suhandi (Politeknik Negeri Jakarta, 2022)
3Dmortar printer is a combination of digital automation technology with cement mortar material technology. The problem that appears in 3Dmortar printer technology requires high financial investment, because this is in the process of development especially in Indonesian, this is to build a 3Dmortar printer machine with a focus on mechanical systems that can function optimally. Design of a 3Dprinter machine with a scale of 1x1x1m was successfully made with the Certasian type which has XYZ axes and has a machine weight of 84kg, can be travel speeds above 25mm/s, the frame used is steel with 40mm and 65mm right angle profiles. The supporting such as an extruder feeder as the regulator of mortar output is a 25mm of diameter nozzle with a 40mm of diameter screw thrust system. Mortar pump as a mortar supplier to an extruder with a hopper capacity of 30kg mortar mix with a 40mm of diameter screw drives the system at 68rpm, output can be obtained at the speed 1070gr/minute